Pathways From Toddler Information Processing to Adolescent Lexical Proficiency. Issue 6 (2nd September 2015) - Rose, Susan A.; Feldman, Judith F.; Jankowski, Jeffery J.
Abstract : This study examined the relation of 3‐year core information‐processing abilities to lexical growth and development. The core abilities covered four domains—memory, representational competence (cross‐modal transfer), processing speed, and attention. Lexical proficiency was assessed at 3 and 13 years with the Peabody Picture Vocabulary Test (PPVT) and verbal fluency. The sample ( N  =   128) consisted of 43 preterms (< 1750 g) and 85 full‐terms. Structural equation modeling indicated concurrent relations of toddler information processing and language proficiency and, independent of stability in language, direct predictive links between (a) 3‐year cross‐modal ability and 13‐year PPVT and (b) 3‐year processing speed and both 13‐year measures, PPVT and verbal fluency. Thus, toddler information processing was related to growth in lexical proficiency from 3 to 13 years.